The hat - Keller, Holly (Orlando, Fla. : Harcourt, 2005)
Simple text tells how Dan helps Pam find her lost hat.
"Ages 4-6; Grade: K-1; Guided Reading Level: B; Reading Recovery Level: 3."
Keywords: Lost and found possessions -- Fiction; Hats -- Fiction